Trends of long-term opioid therapy and subsequent discontinuation among people with chronic non-cancer pain in UK primary care: A retrospective cohort study - Qian Cai; Yun-Ting Huang; Thomas Allen; Charlotte Morris; Christos Grigoroglou; Evangelos Kontopantelis (PLoS ONE, 2025)
Objectives To examine trends of opioid use, focusing on long-term opioid therapy (L-TOT) and its discontinuation among people with chronic non-cancer pain (CNCP). Design and setting Retrospective cohort study using UK Clinical Practice Research Datalink Aurum data. Population Incident opioid users (no opioid use in the prior year) with CNCP between 01/01/2009–31/12/2019. Among them, we identified L-TOT users (≥3 opioid prescriptions within 90 days, or total ≥90 supply days within the first year, excluding the initial 30 days) and L-TOT discontinuers (no opioid use for ≥180 days following a L-TOT). Main outcome measures Yearly rates of incident opioid users (over CPRD-registered patients), L-TOT users (over incident opioid users), and L-TOT discontinuers (over L-TOT users) were calculated. Annual counts of each group were fitted using segmented negative binomial regression models with an offset considering their corresponding denominators from 2009 to 2019, excluding 2014 due to policy changes in that year. Results Among 2,839,161 incident opioid users, 11.4% (n = 324,877) transitioned into L-TOT users within one year, of which 4.8% (n = 15,484) discontinued. Between 2009–2013, rates of L-TOT users significantly declined by 2.6% (incidence rate ratio: 0.974; 95% confidence interval: 0.971 to 0.978) per annum, followed by a significant step change in 2015 (1.026, 1.009 to1.044), and a significant annual increase of 2.4% (1.024, 1.019 to 1.029) from 2015 to 2019, compared to the 2009–2013 trend. The annual rates of L-TOT discontinuers remained stable from 2009 to 2013 (0.987, 0.971 to 1.002), followed by a non-significant step change (0.990, 0.916 to 1.070) in 2015, and a significant decrease in slope by 2.6% (0.974, 0.951 to 0.998) per annum during 2015–2019, relative to 2009–2013. Conclusions L-TOT has plateaued since 2015, accompanied with an accelerated decrease in discontinuation rates, suggesting ongoing reliance on opioids for CNCP management, despite increased awareness regarding L-TOT associated risks. This is likely due to the limited availability of other effective pharmacological options and non-pharmacological alternatives, and challenges in their accessibility.